Dictionary of Filipino culture and values - Andres, Tomas D. (Giraffe Books, 1994)
It aims to make readers see the practical wisdom inherent in the Filipino indigenous cultural and philosophical traditions reflected in Filipino values, and will be able to identify the practical wisdom and articulate the significance and positiveness of the Filipino values operative in his life. Intended for all Filipinos and all those who sympathize with Filipinos as a reference book for their lives, studies and courses. This dictionary includes the positiveness of Filipino culture and values. This is a reference book for Filipinos lives, studies and courses especially the Social Sciences, Behavioral Sciences and Religious Sciences at all levels. It hopes to bridge the gap between Filipinos and their culture and values. The compilation of this dictionary was undertaken because of the need for a dictionary of traditional and contemporary Filipino culture and values which has never been previously published. The author collected definitions, meanings, examples, and articles on Filipino culture and values." The dictionary has 31 subject categories covering the major divisions of knowledge: the natural sciences, the social sciences and humanities. Through this book the reader will see the practical wisdom inherent in the Filipino indigenous, cultural and philosophical traditions reflected in Filipino values, and will be able to identify and articulate the significance and positiveness of the Filipino values operatives in his life. This dictionary is intended for all Filipinos and all those who sympathize with Filipino as a reference book for their lives, studies, and courses, especially the Social Sciences, Behavioral Sciences, and Religious Sciences at all levels.